Stimulasi Ibu dengan Perkembangan Anak Usia 1-2 Tahun di Posyandu Kelurahan Palmeriam - Mirajsul Mirajsul; Mariyani Mariyani (Malahayati Nursing Journal, 2024)
ABSTRACT It is recorded that 52.9 million children are less than 5 years old, it is estimated that 5-25% of preschool-aged children experience minor brain dysfunction including 85,779 (62.02%) fine motor development (WHO, 2018). The Indonesian Pediatricians Association (IDAI) revealed data that it is estimated that 5-10% of children experience developmental delays and 1-3% of toddlers experience global development delays (IDAI, 2013 in Setyaningsih Wahyuni, 2018) so to anticipate this, parents are expected to be stimulated and screened for growth and development as early as possible. To know the relationship Stimulation of mothers with the development of children aged 1-2 years at Posyandu in Palmeriam in 2023. Quantitative study using a cross-sectional method on children aged 1-2 years at posyandu in Palmeriam village. Samples were taken randomly using cluster sampling technique at 10 posyandu as many as 84 respondents. The results of the chi square test showed that the p-value of the relationship between stimulation given by the mother and child development was 0.019 (0.05). The stimulation given by the mother has been shown to have a significant relationship with the development of children aged 1-2 years at Posyandu in Palmeriam Village (H0 is rejected). For further research, it is expected to increase the number of samples so that they can be more representative of the population and health workers can play an active role in providing interventions related to stimulation of development according to the child's age. Keywords: Children, Development, Stimulation  ABSTRAK Tercatat 52,9 juta anak kurang dari 5 tahun, diperkirakan 5-25% anak usia prasekolah mengalami disfungsi otak minor termasuk perkembangan motorik halus sebanyak 85.779  (62,02%) (WHO,2018). Ikatan Dokter Anak Indonesia (IDAI) mengungkapkan data bahwa diperkirakan 5-10% anak mengalami keterlambatan perkembangan dan 1-3% balita mengalami keterlambatan perkembangan umum (global development delay) (IDAI, 2013 dalam Setyaningsih Wahyuni, 2018) sehingga untuk mengantisipasi hal tersebut, diharapkan oran tua  dapat stimulasi dan skrining pertumbuhan dan perkembangan sedini mungkin. Mengetahui hubungan Stimulasi Ibu dengan perkembangan Anak usia  1-2 tahun di posyandu Kelurahan Palmeriam tahun 2023. Penelitian kuantitatif menggunakan metode cross sectional pada anak usia 1-2 tahun di di posyandu Kelurahan Palmeriam. Sampel diambil secara random dengan teknik cluster sampling pada 10 posyandu sebanyak  84 responden. Hasil uji chi square menunjukkan bahwa  nilai p-value hubungan Stimulasi yang diberikan ibu dengan perkembangan anak yaitu 0,019(0,05).  Stimulasi yang diberikan ibu terbukti memiliki hubungan yang bermakna dengan perkembangan anak usia  1-2 tahun di posyandu Kelurahan Palmeriam  (H0 di tolak). Untuk penelitian selanjutkan diharapkan dapat menambahkan jumlah sampel agar dapat lebih mewakili populasi serta nakes dapat berperan aktif memberikan intervensi terkait Stimulasi perkembangan sesuai usia anak. Kata Kunci: Anak, Perkembangan, Stimulasi